The personal correspondence of Hildegard of Bingen - Hildegard, Bingen, Äbtissin, Heilige (Oxford University Press, 2006)
Reaching out -- Criticism and response -- Richardis von Stade -- Hildegard's spreading reputation -- Exorcism -- Family -- A fellow visionary -- A sermon -- The Provost Volmar, and the controversy after his death -- Miscellaneous letters and visions -- Guibert of Gembloux